Biomechanics and Functional Tissue Engineering - Haidar, Ziyad S.; Abdurakhmonov, Ibrokhim Y.; Barkaoui, Abdelwahed (IntechOpen, 2021)
Biomechanics and Functional Tissue Engineering is a useful resource for scientists, researchers, engineers, and clinical practitioners involved in bioengineering solutions for improved patient quality of life. It focuses on the potentially impactful role of applied and functional bio-dental tissue engineering, drug/gene delivery (controlled and metered systems) and cell therapy, bioscaffolds, image-guided and image-assisted surgery, nanodentistry, and biomechanics towards developing better solutions for problems and conditions of the orodental and cranio-maxillofacial complex and beyond.